Temperature effects on material characteristics - Murphy, A. J.; Kennedy, A. J. (College of Aeronautics, 1960)
Some of the physical properties of the main elements of interest in high temperature technology are reviewed. Some general trends emerge when these properties are viewed as a function of melting point, but there are a few notable exceptions. Titanium, zirconium, niobium and tantalum all have disappointingly low moduli; chromium is excellent in many ways, but has a limited ductility at lower temperatures; molybdenum oxidises catastrophically above about 700° C, and niobium suffers from severe oxygen embrittlement. Beryllium and carbon (in the graphitic form) both stand out as exceptional materials, both have very low densities, beryllium a very high modulus but an unfortunately low ductility, while graphite has a relatively low strength at the lower temperatures, although at temperatures of 2000° C and above it emerges as a quite exceptional (and probably as the ultimate) high temperature material. Some of the fundamental factors involved in high temperature material development are examined, in the light, particularly, of past progress with the nickel alloys. If a similar progress can be achieved with other base elements then a considerable margin still remains to be exploited. Protection from oxidation at high temperatures is evidently a factor of major concern, not only with metals, but with graphite also. Successful coatings are therefore of high importance and the questions they raise, such as bonding, differential thermal expansion, and so on, represent aspects of an even wider class covered by the term “composite structures". Such structures appear to offer the only serious solution to many high temperature requirements, and their design, construction and utilization has created a whole series of new exercises in materials assessment. Matters have become so complex, that a very radical and fundamental reassessment is required if we are to change, in any very significant way, the wasteful and ad hoc methods which characterise so much of present-day materials engineering.